Profil Kebahagiaan Remaja Panti Asuhan Tasikmalaya serta Implikasi terhadap Layanan Konseling - Gian Sugiana Sugara; Agrissha Meidianty Rahayu; Cucu Arumsari (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2021)
Research related to the profile of adolescent happiness aims to create a solution to increase adolescent happiness in the Tasikmalaya orphanage. The increasing cases of depression experienced by teenagers prompted the authors to conduct research on the profile of adolescent happiness in general. Therefore, this study uses quantitative research with descriptive studies. The data measurement tool uses a questionnaire that has been constructed based on Martin Seligman's latest Authentic Happiness Inventory. With a population of 92 orphanages in Tasikmalaya, the results of the study are as follows: in general, the happiness level of adolescents in social orphanages in Tasikmalaya city is in the moderate category; based on gender is in the moderate category and there is no difference between the two. Recommendations for administrators of social care homes in the city of Tasikmalaya is that the design of the implementation of guidance and counseling services based on penn resilience programs that have been listed in this study can be implemented by administrators of social care institutions in the city of Tasikmalaya to increase the happiness of adolescents in social care institutions.